Garden show - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a garden at a garden show. Included in the garden is a stone retaining wall and a stone patio around a pond. Material from a large tent appears above and behind this scene. A narrow long banner with a design of ancient Roman warriors, chariots and horses hangs in the background. A small sign in the right foreground reads, "Cole's Nursery."